Tingkat Pengetahuan Tentang Hepatitis B pada Mahasiswa Praktik Klinik JKG Poltekkes Kemenkes Yogyakarta - asrori ibnu, ibnu (Journal of Oral Health Care, 2021)
Hepatitis is one of health issues found around the world, including Indonesia. This disease comprises five types: Hepatitis A, B, C, D, and E. As a medical personnel, a nurse, especially a dental nurse, can prevent any possible contact with the infectious substance if they have proper knowledge of the contagion of the Hepatitis B virus. This research aims to find out the level of knowledge on Hepatitis B amongst the internships of JKG Poltekkes Kemenkes Yogyakarta. The study is an analytic-comparative research in nature with the cross sectional approach. This approach is a type of research in which the research object is only observed once and the measurement is done towards the character status or the subject variable at the examination. This design can reveal which one becomes the exposure and its cause and effect relationship is evident: to find out the level of knowledge on Hepatitis B amongst the internships of the clinic of JKG Poltekkes Kemenkes Yogyakarta. Therefore, it can be concluded that the majority of the students who became the interns already had sufficient knowledge about the Hepatitis B virus.